Length-weight relationships, condition factor and growth parameters of Periophthalmus chrysospilos (Bleeker, 1852) (Gobiiformes: Gobiidae) in Bayan Bay, Penang, Malaysia - Mohd Ilman Che Abdullah; Khaironizam Md Zain (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study reports the length-weight relationships (LWR), body condition factor (Kn) and growth parameters of Periophthalmus chrysospilos in Bayan Bay of Penang, Malaysia. The values of exponent b for all categories of fish were higher than 3 indicating a positive allometric growth. The mean condition factor (Kn) for all categories of fish also higher than 1 which reflect the well beings of fish in the study area. The b values of LWR and condition factors for male was similar to female fish, but the b values of LWR and condition factors were significantly higher in rainy months compared to the dry months. The parameters of population dynamic show the asymptotic length (L∞) of 13.20 cm, growth coefficient (K) of 0.68 year-1, growth performance index (Ø’) of 2.074, total mortality (Z) of 2.47 year-1, and fishing mortality (F) of 0.70 year-1. The exploitation level (E) was 0.28 year-1 indicating of low exploitation and estimation of length at first capture was 7.69 cm. The annual recruitment pattern of P. chrysospilos was recruited in two peaks per year.